Analisis Yuridis Terhadap Perjanjian Waralaba (Franchise) dalam Perspektif Keadilan Kontraktual di Indonesia - Daniela Rica Bairam (Advokasi Hukum & Demokrasi (AHD), 2026)
A franchise agreement is a form of contractual legal relationship that is strategically significant in the development of businesses in Indonesia, particularly in the retail, service, and food and beverage sectors. This relationship binds the franchisor and franchisee in managing interrelated rights and obligations. Although the number of franchise businesses has increased significantly, the practice of standard agreements unilaterally drafted by franchisors often creates contractual injustice, where franchisees have weaker bargaining positions. This phenomenon is further exacerbated by the lack of harmony between the older regulation, Government Regulation No. 42 of 2007, and newer regulations, namely Government Regulation No. 35 of 2024 on Franchising and Government Regulation No. 28 of 2025 on risk-based licensing, which introduce more detailed mechanisms of supervision and legal protection but still pose implementation challenges in practice. This study employs a normative juridical approach through analysis of statutory regulations, recent legal literature, and franchise contract documents as data sources. The analysis focuses on the principles of contractual justice, the balance of rights and obligations of the parties, and the effectiveness of the latest regulations in protecting franchisees from unfair contractual practices. The results indicate that although the new regulations clarify the rights and obligations of franchisors and franchisees, as well as procedures for termination and compensation, contractual imbalances still occur, particularly in SME franchise businesses. Therefore, strengthening legal literacy among franchise actors, increasing contract transparency, and active government supervision are strategic solutions to achieve effective contractual justice.